Clostridium perfringens Iota-Toxin Requires Activation of Both Binding and Enzymatic Components for Cytopathic Activity - Gibert, Maryse (American Society for Microbiology, 2000)
Iota-toxin is produced by Clostridium perfringens type E strains and consists of two independent components, the enzymatic and binding components, referred to as Ia and Ib, respectively. A recombinant C. perfringens strain, strain 667/pMRP147, produced processed Ia and partially processed Ib, while a recombinant C. perfringens type A strain, strain TS133/pMRP147, in which the VirR-VirS two-component system is inactivated, produced only precursor forms of Ia and Ib. This suggests that iota-toxin is processed by a VirR-VirS-responsive protease, although not completely in the recombinant type A strain. The precursor forms of Ia and Ib were purified from cultures of the latter strain, and their proteolytic activation was examined. Treatment with proteases cleaved off small peptides (9 to 13 amino acid residues) and a 20-kDa peptide from the N termini of the Ia and Ib precursors, respectively, leading to their active forms. They were activated efficiently by α-chymotrypsin, pepsin, proteinase K, subtilisin, and thermolysin but only weakly by trypsin, as demonstrated by the cell-rounding assay. λ-Protease from the C. perfringens type E strain, which was found to be a zinc-dependent protease related to thermolysin, activated iota-toxin as efficiently as did α-chymotrypsin. These results suggest that λ-protease is most responsible for the activation of iota-toxin in type E strains.